ANALISIS MOTIVASI BELAJAR SISWA TERHADAP PEMBELAJARAN FPB DAN KPK DENGAN MENGGUNAKAN VBA FOR EXCEL - Anita Oktavia Salbiah; Ani Ainun Masruroh; Siti Chotimah (IKIP Siliwangi, 2021)
The study was conducted in MIM Saar 02 with a total of 31 students aiming to find out how to study students ' motivation for mathematical learning on FPB and KPK materials by using VBA Media for Excel. The method used is qualitative descriptive with the instruments of a learning motivation questionnaire with 9 learning motivation indicators consisting of 10 positive statements and 10 negative statements. From the study, it was obtained that the motivation to learn students about the learning of FPB and KPK by using VBA Media for Excel was very high. And the highest indicator is flexible in doing mathematical work of 96.78%. And the score that most students have gained is at intervals 2.66 – 3.65 with the category good.